Особенности систем автоматизированного контроля и слежения за нераспространением радиоактивных материалов - Буртняк, В.М. (Моделювання та інформаційні технології, 2009)
The analysis of the automatic system of monitoring and tracing for radiation
materials is resulted. Their basic descriptions are resulted.